THE DODDERING (Lupinus mutabilis Sweet) NUTRITIONAL COMPLEMENT IN GESTANTES ADOLESCENTS. AMARYLLIS. HUÁNUCO - 2009 - Soto Rueda, Ana M. (2017)
Experimentally we determine the nutritional value of the doddering one (Lupinus mutabilis Sweet) like nutritional complement in undernourished early adolescent gestantes. For it was chosen it to four gestantes starting from the 4 ° month of pregnancy, distributed in group TO and C (control) in same number. The doddering one was administered via oral in salad form to reason of 100 gr. newspaper for 90 serial days to the group TO, while to the group control he/she was offered orientation and consejería it has more than enough nutrition. The weight was calculated before the gestation, during the I, II and III trimester, with the chart of gain of weight for gestantes, normado for the Ministry of Health. When carrying out the evaluation at the end of the investigation, it was observed that the gestantes of the group TO, to which it was applied the I stimulate they increased their weight corresponding to the pregnancy, and a slight increment that corresponds to the frequency of 4%, something significant, like complement nutritional sumatorio, in comparison with the group control, where the gestantes, only increased the weight corresponding to the gain of the pregnancy, demonstrating that the doddering one is a not very significant nutritional complement in the diet of the pregnant one.